Structural and mechanical properties of YBaCo4O7+δ thin films deposited on c-Al2O3 substrates by dc magnetron sputtering. Issue 10 (December 2015) - Gómez, A.; Izquierdo, J.L.; Astudillo, A.; Martinez, J.; Bolaños, G.; Meza, J.M.; Isaza, C.; Mesa, C.; Morán, O.
Abstract: High-quality YBaCo4 O7+ δ powders were obtained by standard solid-state reaction. The powders were pelletized and sintered at 1300 °C. The targets were subsequently coupled to a dc magnetron sputtering cannon using commercial silver epoxy. YBaCo4 O7+ δ thin films (~100 nm) were then grown on c -Al2 O3 single-crystal substrates heated at 750, 800 and 850 °C. Microstructural analysis was carried out by means the X-ray diffraction measurements. A strong dependence of the crystalline quality of the thin films on the substrate temperature was evidenced. In turn, Young׳s modulus and nanohardness values of YBaCo4 O7+ δ, both in bulk and thin film form, were determined by means of nanoindentation measurements. The values of Young׳s modulus and hardness obtained for YBaCo4 O7+ δ in bulk form were in good agreement with those encountered for thin films. Before the deposition of the films, the thermal expansion coefficients of the YBaCo4 O7+ δ target and the sapphire substrates were determined using a dilatometry technique. The thermal expansion coefficients of the target and the sapphire substrates ended up being very close each to other, which favors the growing of the thin films. Finally, the lattice strain, the lattice deformation stress and the deformation density energy of the thin films were also estimated from the X-ray diffraction measurements using the Williamson–Hall model. The achieved results show that the Williamson–Hall methodology is a good alternative method to estimate stress and mechanical properties of materials in thin film form.